Sistemas de informação: um enfoque gerencial - Moreira, Pedro Adolfo Moreno da Costa (2019)
The research deals with aspects of judicial activism, an institute that has been providing a new north for the realization of rights and prerogatives established in the Federal Constitution, and, immediately, putting in question the traditional tripartition of Powers. In this toar, after the successive evolutions of Constitutionalism, the Judiciary not only became what was once called the Moderating Power, but also promoted a dynamics within the State structure capable of providing the constitutional effectiveness directly performed by the Judiciary , by means of a pro activity and a protagonism that until then did not exist within the State Scenario. It is in the midst of this pro activity of the Judiciary that more and more the rights hitherto or evaded or ill rendered by the Legislative and Executive Powers, are finding shelter through this direct intervention of the Judiciary, that classically was jungled to the principle of inertia of jurisdiction. Based on this understanding, the work has the desire to verify if the STF judgments maintain a line of thought in cases that involve the right to health. For that, the methods of historical and monographic procedures and the techniques of bibliographic and documentary research are used, imparting a research of a methodological and qualitative nature, seeking to better understand judicial activism and its role of modifying the Structure of the State, in order to , in sequence, to enable the confirmation, of the realization of constitutional rights starting from this new action of the Judiciary to enforce the constitutional directives. In addition, the role of the Judiciary, in particular, of the Federal Supreme Court in solutions to violations of the Right to Health is attached to the work, so as to establish, from the analysis of Supreme Court judgments, a jurisprudential profile of the Court when of the judgment of matter to the Right to Health, especially when using the technique of judicial activism to implement rights to the citizen.